New evidence in favor of the abiogenic genesis of hydrocarbons from the results of the testing of direct-pros pecting methods in various regions of the world - Yakymchuk, M.A.; Korchagin, I.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The results of experimental studies using mobile methods of frequency resonance processing and interpretation of satellite images and photo images in various regions of the world are summarized. The studies were carried out with the aim of improving the methodology of the use of direct-prospecting methods in the geological exploration process for oil and gas, as well as studying the possibility of their application to detect the areas of accumulation of hydrogen, various minerals, and chemical elements. Within the survey areas, a significant number of deep channels (volcanoes) of migration of fluids, minerals, and chemical elements, filled with sedimentary and igneous rocks, including salt, were found. The roots of volcanoes, filled with sedimentary, igneous, and metamorphic rocks, are almost always fixed at depths of 996, 723, 470, 195-217, and 95 km. The interval 195-217 km is a layer of the plastic state of rocks. It has been established that the responses (signals) at the resonant frequencies of oil, condensate, and gas are recorded only in areas, where the channels (volcanoes) are filled with certain groups of sedimentary and igneous rocks. In the survey areas, in which the responses from the HC are recorded, within (in the central parts) of the channels (volcanoes) of the deep fluid migration, a boundary of 57 km is almost always recorded. Below this boundary, the responses are recorded at the frequencies of hydr ogen and carbon, above that of oil, condensate, gas, and amber (only in channels of a certain type). The super-operational method of integrated assessment of the prospects for the presence of oil, gas, and ore provides an opportunity to significantly accelerate and optimize the geological exploration process for combustible and ore minerals. The proven mobile technology of frequency-resonance processing of satellite images and photo images is recommended for the use in Ukraine (as well as in other regions of the world) for the purpose of a preliminary assessment of the prospects of the oil and gas content and the ore content of poorly studied and unexplored search blocks and local sites.